Thailand’s Foreign Direct Investment (FDI) in Vietnam - Suvakunta, Pittaya (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
The similarities between Thailand and Vietnam can be seen in the countries’ geographical features, society, cultural proximity, economy, and the bond between the citizens of the two countries. The diplomatic relationship between Thailand and Vietnam was established in 1976 and continues to get stronger. In 1986, Vietnam implemented the “Doi Moi” policy to reform the socialist market economy which paved the way to economic relationship, the legislation on investments, and exposure to foreign investments. Thailand started investment in Vietnam in the 1980s, which increased during the 1990s. However, in 1997, the investment declined due to the economic crisis in Thailand. When the crisis passed, Thailand's investment in Vietnam was revived in the late 2000s, and was rated one of the top 10 foreign investors in Vietnam. It has now been 4 decades since Thailand and Vietnam founded their relationship. There are three factors related to investment, namely: 1) Geographical factors; 2) Political factors; and 3) Economic factors. Such factors can affect the development of relationship between Thailand and Vietnam, and the cooperation within ASEAN countries. These factors motivate Thailand’s Foreign Direct Investment (FDI) to Vietnam from 1976 to 2016. This paper aims at suggesting some feasible solutions to encourage higher market size, GDP growth, openness to trade and better infrastructure development that strengthens Economic Cooperation (EC) between East Asia and Southeast Asia, and to work constructively together for the common benefit of the region in the future.